Synthesis of magnetic cobalt Nanoparticles anchored on graphene nanosheets and catalytic decomposition of orange II - Yao, Yunjin; Xu, C.; Qin, J.; Wei, F.; Rao, M.; Wang, S. (American Chemical Society, 2013)
Magnetic cobalt nanoparticles (NPs) at a size of approximately 29.9 nm anchored on graphene sheets were prepared and tested for heterogeneous oxidation of a dyeing pollutant, Orange II, with peroxymonosulfate (PMS) in aqueous solutions. The physicochemical properties of Co–graphene hybrids were investigated by various characterization techniques, such as powder X-ray diffraction (XRD), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectrometer (EDS), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The incorporation of Co NPs and graphene sheets produces much higher catalytic activity of Orange II degradation than pure Co. The Orange II decomposition rate increases with increasing temperature (25–45 °C), pH (4–10), and PMS dosage (0.04–0.60 g/L) but decreases with its increased concentration (30–120 mg/L). Kinetic studies show decomposition of Orange II on Co–graphene can be described by a pseudo-first-order kinetic model with activation energy of 49.5 kJ/mol.